Development of breeding lines with three pyramided resistance genes that confer broad-spectrum bacterial blight resistance and their molecular analysis in rice - Suh, Jung-Pil; Jeung, Ji-Ung; Noh, Tae-Hwan; Cho, Young-Chan; Park, So-Hyun; Park, Hyun-Su; Shin, Mun-Sik; Kim, Chung-Kon; Jena, Kshirod K. (Springer, 2013)
The development of resistant cultivars has been the most effective and economical strategy to control bacterial leaf blight (BB) disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo). Molecular markers have made it possible to identify and pyramid valuable genes of agronomic importance in resistance rice breeding. In this study, three resistance genes (Xa4 + xa5 + Xa21) were transferred from an indica donor (IRBB57), using a marker-assisted backcrossing (MAB) breeding strategy, into a BB-susceptible elite japonica rice cultivar, Mangeumbyeo, which is high yielding with good grain quality.Our analysis led to the development of three elite advanced backcross breeding lines (ABL) with three resistance genes by foreground and phenotypic selection in a japonica genetic background without linkage drag. The background genome recovery of the ABL expressed more than 92.1% using genome-wide SSR marker analysis. The pathogenicity assays of three resistance-gene-derived ABL were conducted under glasshouse conditions with the 18 isolates of Xoo prevalent in Korea. The ABL exhibited very small lesion lengths, indicating a hypersensitive reaction to all 18 isolates of Xoo, with agronomic and grain quality traits similar to those of the recurrent parent. Pyramiding the resistance genes Xa4, xa5 and Xa21 provided a higher resistance to Xoo than the introduction of the individual resistance genes. Additionally, the combination of two dominant and one recessive BB resistance gene did not express any negative effect on agronomic traits in the ABL.The strategy of simultaneous foreground and phenotypic selection to introduce multiple R genes is very useful to reduce the cost and the time required for the isolation of desirable recombinants with target resistance genes in rice. The resistance-gene-derived ABL have practical breeding value without a yield penalty by providing broad-spectrum resistance against most of the existing isolates of BB in South Korea and will have a high impact on the yield stability and sustainability of rice productivity.